Ks. Wincenty Myszor, Gnostycyzm i teologia Ireneusza z Lyonu: zagadnienia wybrane, red. Ludmiła Lach-Bartlik, SACh NS 11, Katowice 2010, Księgarnia św. Jacka, ss. 384. - Zmorzanka, Anna Z. (Vox Patrum, 2011)
nie dotyczy